2015
DOI: 10.1038/aps.2015.45
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency stimulation of the external globus palladium produces anti-epileptogenic and anti-ictogenic actions in rats

Abstract: Low-frequency stimulation, but not high-frequency stimulation, at the GPe exerts therapeutic effect on temporal lobe epilepsy and tonic-colonic generalized seizures, which may be due to interference with delta rhythms. The results suggest that modulation of GPe activity using low-frequency stimulation or drugs may be a promising epilepsy treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Low but not high frequency stimulation of GPe has a neuroprotective preventive effect in an amygdala-kindling model in rats with less than half of the rats (43%) showing fully kindled symptoms compared to high frequency simulated rats (89%) and control group (100%). Furthermore, the cumulative after-discharge duration and generalized seizure duration in the low frequency stimulated group was significantly shorten compared to the high frequency or control group (Cheng et al 2015). These effects were suggested to be mediated through a normalization of the oscillatory power in the amygdala via the NAcc.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Low but not high frequency stimulation of GPe has a neuroprotective preventive effect in an amygdala-kindling model in rats with less than half of the rats (43%) showing fully kindled symptoms compared to high frequency simulated rats (89%) and control group (100%). Furthermore, the cumulative after-discharge duration and generalized seizure duration in the low frequency stimulated group was significantly shorten compared to the high frequency or control group (Cheng et al 2015). These effects were suggested to be mediated through a normalization of the oscillatory power in the amygdala via the NAcc.…”
Section: Introductionmentioning
confidence: 94%
“…Interestingly, albeit smaller, comparable neuroprotective effects were found with injections into the SNr and the striatum (Klitgaard et al 2003). The GPe that receives direct GABAergic projection from the NAcc seems to also play a major role in the control of TLE (Cheng et al 2015; Robertson and Jian 1995). Low but not high frequency stimulation of GPe has a neuroprotective preventive effect in an amygdala-kindling model in rats with less than half of the rats (43%) showing fully kindled symptoms compared to high frequency simulated rats (89%) and control group (100%).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies described LFS induces a transient synaptic depression that alters synaptic transmission [45]. Further, LFS in the GPe exerts therapeutic effect on seizures due to interference with delta rhythms [78]. LFS could modulate cortical oscillations with statedependent [79].…”
Section: Mechanism Of Low Frequency Dbsmentioning
confidence: 99%
“…Structures such as the amygdala may be more susceptible to kindling than other structures such as the hippocampus 29 . In addition, in the present study, LFS was applied at the primary focus instead of a secondary focus, because (1) the locations and numbers of PTS events are always unpredictable in a clinical setting 4 , 5 , 30 , (2) LFS targeted outside of the seizure focus showed promising anti-epileptogenic effects 16 , 17 , (3) LFS targeting the primary focus may provide wider coverage of anti-epileptic effects and less additionally invasive lesions. Taken together, these conjectures indicated that LFS targeting the primary focus is a promising approach to inhibit PTS at multiple secondary foci.…”
Section: Discussionmentioning
confidence: 99%